Pollen viability restoration in a Coffea canephora P. and C. heterocalyx Stoffelen backcross. QTL identification for marker-assisted selection - Coulibaly, I; Louarn, J; Lorieux, Mathias; Charrier, A; Hamon, S; Noirot, M (2003)
Male fertility of interspecific hybrids was analysed in one F1 and two backcrossed progenies originating from a cross between Coffea canephora and Coffea heterocalyx. Male fertility was tested using pollen stainability with acetic carmine. The results showed a marked decline in fertility at the F1 level, and fertility was almost fully restored after two backcrosses. The computed broad-sense heritability represented 47% of the variance. Quantitative trait loci (QTLs) locations and effects on pollen viability were estimated using an amplified fragment length polymorphism (AFLP) genetic linkage map constructed in the segregating BC1 population. Three significant QTLs (LOD>3 and p < 0.001 by ANOVA) were detected for pollen viability, two of which were responsible for the bimodal distribution of pollen viability in the segregating population. One QTL was involved in fertility variations among fertile BC1 plants. Fertility inheritance is discussed in relation with previously demonstrated chromosomal sterility in Coffea hybrids and the effect of detected QTLs. The potential use of genetic markers to overcome sterility in interspecific hybrids is also discussed.